Temporal distancing during the COVID‐19 pandemic: Letter writing with future self can mitigate negative affect. Issue 2 (17th February 2021) - Chishima, Yuta; Huai‐Ching Liu, I‐Ting; E. Wilson, Anne
Abstract: Novel coronavirus disease (COVID‐19) is spreading across the world, threatening not only physical health but also psychological well‐being. We reasoned that a broadened temporal perspective may attenuate current mental distress and tested a letter‐writing manipulation designed to connect people to their post‐COVID‐19 future selves. We conducted an online experiment with 738 Japanese participants recruited from two common survey platforms. They were randomly assigned to either send a letter to their future self ( letter‐to‐future ) condition, send a letter to present self from the perspective of future self ( letter‐from‐future ) condition, or a control condition. Participants in both letter‐writing conditions showed immediate decrease in negative affect and increase in positive affect relative to the control condition. These effects were mediated by temporal distancing from the current situation. These findings suggest that taking a broader temporal perspective can be achieved by letter writing with a future self and may offer an effective means of regulating negative affect in a stressful present time such as the COVID‐19 pandemic.